1987
DOI: 10.1083/jcb.105.6.3031
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of cardiac ventricular myosin heavy chain homodimers and heterodimers by monoclonal antibody epitope mapping.

Abstract: Abstract. Two mAbs, one specific for cardiac a-myosin heavy chains (MHC) and the other specific for cardiac 13-MHC, were used to investigate the heavychain dimeric organization of rat cardiac ventricular myosin. Epitopes of the two mAbs were mapped on the myosin molecule by electron microscopy of rotary shadowed mAb-myosin complexes, mAbs were clearly identifiable by the different locations of their binding sites on the myosin rod. Thus, myosin molecules could be directly discriminated according to their r or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…Therefore, the dominant negative effect observed in these mutant cells is associated with the presence of singleheaded myosin II Although nothing is known about the mechanisms of coiledcoil formation in vivo, it is likely that the dimerization of two MHC peptides occurs post-translationally. This hypothesis is supported by the presence of myosin heterodimeric molecules in rat cardiac tissue and smooth muscle (19,20). Our results also support this hypothesis since we find heterodimeric singleheaded myosin molecules.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the dominant negative effect observed in these mutant cells is associated with the presence of singleheaded myosin II Although nothing is known about the mechanisms of coiledcoil formation in vivo, it is likely that the dimerization of two MHC peptides occurs post-translationally. This hypothesis is supported by the presence of myosin heterodimeric molecules in rat cardiac tissue and smooth muscle (19,20). Our results also support this hypothesis since we find heterodimeric singleheaded myosin molecules.…”
Section: Discussionsupporting
confidence: 81%
“…This failure to trigger a change in the molecular regulation of other contractile protein genes is similar to the lack of response elicited from overexpression of the skeletal Tn-C isoform in the heart (36). Interestingly, overexpression of the wild type ␣-MHC exhibits limited, if any, cardiac abnormalities, 3 a result similar to our findings with the ␣-MHC/␤-TM transgenic mice. Thus, it appears that overexpression of contractile protein genes in vertebrates may lead to physiological changes in cardiac function, 3 L. Leinwand, personal communication.…”
Section: Figsupporting
confidence: 79%
“…Significant motility of eGFP-myosin fusions was also shown previously (Reisen and Hanson, 2007;Sparkes et al, 2008). Heterodimers of myosins were detected in low percentage in different systems; however, it was shown that homodimers are more thermodynamically stable (Dechesne et al, 1987;Kerwin and Bandman, 1991;Singh and Bandman, 2006), and heterodimerization of plant myosins is still to be tested. Interestingly, heterologous interaction between two subdomains of the globular tails GT1 from MYA1 and GT2 from MYA2, XI-C, or XI-K was observed in yeast two-hybrid analysis (Li and Nebenfü hr, 2007).…”
Section: Discussionmentioning
confidence: 88%